La expedición directa en acuerdos comerciales: actual postura de la SUNAT y reflexiones sobre su correcto cumplimiento - Ruiz Rosado, Mauricio (2023)
Currently, Superintendencia Nacional de Administración Tributaria (SUNAT) continues to focus on maintaining a rigid performance of its control function. Despite having the tools and means to exchange information with customs authorities around the world, it makes languid efforts to facilitate the accreditation of direct shipment and the access to tariff benefits.In this article, the author analyzes that the position adopted by SUNAT hinders the transportation of goods in import activities. He also reflects on the uncertainty that exists in the delimitation of competence between SUNAT and MINCETUR to issue technical opinions.